Integration of STEAM Approach and Local Wisdom in Early Childhood Education - Eka Setiawati; Yusdiana Yusdiana; Ayu Fajarwati; Yuyun Yuningsih; Yeti Nurdiati (CV. Edujavare Publishing, 2026)
The study is based on the growing need for educational practices that not only develop twenty-first-century competencies but also preserve cultural values and local identities. This study aims to examine the integration of the Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach and local wisdom in early childhood education through a library research method. This study employed a library research method with a qualitative descriptive approach. Data were collected from various scholarly sources, including journal articles, books, conference proceedings, and policy documents related to STEAM education, local wisdom, and early childhood learning. The collected literature was analyzed using content analysis to identify key concepts, implementation strategies, benefits, and challenges associated with the integration of STEAM and local wisdom. The findings of this study indicate that STEAM learning fosters critical thinking, creativity, collaboration, communication, and problem-solving skills through interdisciplinary activities and experiences. Meanwhile, local wisdom provides meaningful cultural contexts that strengthen children’s cultural identity, environmental awareness, and appreciation of community values. The integration of STEAM and local wisdom creates culturally responsive learning experiences that support holistic child development while fostering both global competencies and local cultural preservation. Therefore, this integrated approach can serve as an innovative and sustainable educational model for enhancing the quality of early childhood education in diverse cultural settings.